2018
DOI: 10.21595/jve.2018.19373
|View full text |Cite
|
Sign up to set email alerts
|

Free longitudinal vibrations of functionally graded tapered axial bars by pseudospectral method

Abstract: In this work, the problem of free longitudinal vibration of rods with variable cross-sectional area and material properties is investigated using the pseudospectral method. With the gradation of material properties like modulus of elasticity and mass density in the axial direction, the results corresponding to a functionally graded axial bar are obtained using the proposed pseudospectral formulation. The pseudospectral formulation used is relatively easy to implement and powerful in analyzing vibration problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…As shown in Table 20, the results obtained from this study are in very good agreement with [28], even with 20 subdomains. However, for further research, additional computations were conducted, and the results shown in Tables 21-23 were obtained according to different combinations of boundary conditions.…”
Section: Modesupporting
confidence: 78%
See 4 more Smart Citations
“…As shown in Table 20, the results obtained from this study are in very good agreement with [28], even with 20 subdomains. However, for further research, additional computations were conducted, and the results shown in Tables 21-23 were obtained according to different combinations of boundary conditions.…”
Section: Modesupporting
confidence: 78%
“…Pillutla et al [28] studied the longitudinal vibrations of functionally graded rods with variable cross-sectional areas and material properties using the pseudospectral method.…”
Section: Calio and Elishakoffmentioning
confidence: 99%
See 3 more Smart Citations